PENGARUH KUALITAS APARATUR DAERAH, REGULASI, SISTEM INFORMASI DAN KOMITMEN TERHADAP MANAJEMEN ASET - Rosihan Rosihan; Bonifasia Elitha Bharanti; Westim Ratang (Universitas Cenderawasih, 2017)
Each region are required to be able to manage asset efficiently and effectively. For that, this research is conducted in the government of Papua province with an examination of the influence of the quality of local officials, regulations, information system for asset managements, and commitment to the asset management. A method of descriptive applied by using questionnaire for data collection and regression to data analysis. The results of the research showed that the quality of apparatus significant and positively correlate. Hence, increasing the quality of apparatus needs to be improved through formal education and relevant technical training. Another thing to do is placement staff has to be in accordance with competence. Regulating factor showed a positive and significant influence and the binding regulations existence become a weighted point in handling regional assets. Information systems factor has a positive and significant impact for assets managements in government of Papua province. Information technology application usage has to be an important part for managing regional assets because of efficient and accurate. Leaders' commitment factor have a positive and significant impact, so that the head of SKPD which is responsible for asset usage has to make written commitment as a pact of integrity. Five factors are to be considered in managing regions assets, so that attention and act are required to increase those five factors as well. Keyword : assets management, quality of local officials, regulation, information system, leaders commitment, government of Papua province